2016
DOI: 10.5792/ksrr.16.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiological Parameters between Normal and Patellar Dislocation Groups in Korean Population: A Rotational Profile CT-Based Study

Abstract: PurposePatellofemoral instability is a common cause of anterior knee pain in adolescents and young adults. Most normal and pathological values for diagnosing patellofemoral instability are based on Western literature. We conducted this radiological study to determine normal values for different patellofemoral parameters in a Korean population and to evaluate their usefulness in diagnosis.Materials and MethodsWe retrospectively reviewed the rotational profile computerized tomography (CT) scans of the patellar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 26 publications
6
51
3
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19] These included six publications that compared between cartilaginous and bony sulcus angles, 9,11,13,15,17,18 and eight publications that compared between sulcus angles for patients with and without patellofemoral instability. 9,10,12-14, 16,18,19 Collectively, these included a total of Table 1 Details of the studies included in the review 1,204 patients, of which 693 had patellofemoral instability, while 511 did not have patellofemoral instability. The details of the study design and patient population of all the studies are reported in ►Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18][19] These included six publications that compared between cartilaginous and bony sulcus angles, 9,11,13,15,17,18 and eight publications that compared between sulcus angles for patients with and without patellofemoral instability. 9,10,12-14, 16,18,19 Collectively, these included a total of Table 1 Details of the studies included in the review 1,204 patients, of which 693 had patellofemoral instability, while 511 did not have patellofemoral instability. The details of the study design and patient population of all the studies are reported in ►Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2 This has led to two commonly used sulcus angle measurements, which are the cartilaginous sulcus angle and the bony sulcus angle. [9][10][11][12][13][14][15][16][17][18][19] Multiple studies have been conducted to analyze whether the cartilaginous and bony sulcus angles are interchangeable or different. All six publications included in the review reported the cartilaginous sulcus angle to be greater than the bony sulcus angle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations